Penggunaan Data Curah Hujan Satelit Global Precipitation Measurement (GPM) Untuk Analisa Hidrologi Perencanaan Embung di Indonesia - Dandy Achmad Yani; Moh Abduh; Azhar Adi Darmawan; Suwignyo Suwignyo (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Indonesia is committed to supporting national strategic programs, one of which is food self-sufficiency. Therefore, to achieve optimal irrigation during the dry season, planning for reservoir construction is necessary. One crucial analytical activity in reservoir planning is hydrological analysis. This analysis determines the structural design requirements and the extent of the reservoir's irrigation benefits, provided sufficient data is available. Unfortunately, rainfall data from observation posts is sometimes incomplete, necessitating the use of satellite rainfall data. This study aims to analyze the potential use of Global Precipitation Measurement (GPM) satellite rainfall data as a primary source of hydrological analysis for reservoir planning, particularly in determining the design flood discharge for the return period. The limited availability of observed rainfall data in Indonesia is a major obstacle in the water structure planning process, particularly in rural areas and upstream river basins (DAS).